ANALYSIS OF TRAFFIC ACCIDENTS IN THE WEST SURABAYA REGION (CASE STUDY: KALIANAK ROAD TO ROMOKALISARI HIGHWAY) - Eka Safitri; Hadi Putra, Kurnia; Chandra Agusdini, Theresia Maria (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
The high volume of heavy vehicle traffic on Kalianak Street, Greges, Tambak Langon, Tambak Osowilangun and Romokalisari causes the roads to become increasingly congested, which causes frequent traffic accidents. Accident data used for 2017, 2018, 2019, 2020, 2021 and 2022 to determine accident-prone areas using the z-score method, the number of accidents for each level of victim severity using the Accident Rate method and to determine the amount of loss caused by accidents using the Gross method Output (Human Capital). The results of the analysis show that the highest number of accidents was in 2017 - 2016 for the classification of deaths, serious injuries and minor injuries on Romokalisari Street with an accident rate of 0.246 people per 1 million vehicle kilometers per year, the classification of seriously injured victims was 0.092 people per 1 million vehicle kilometers per year in Kalianak and minor injury victims of 0.406 people per 1 million vehicle kilometers per year on Romokalisari Street. The accident-prone area (Blacksite) with the largest value is the Tambak Osowilangun Z-Score for 6 years of 1.45 and the last year of 1.14. Total costs for accident victims based on the Gross Output (Human Capital) method for each year; 2017 amounting to IDR 12,529,506.23, in 2015 IDR 11,439,656,822, in 2019 IDR. 13,324,550,588, 2020 Rp. 11,010,983,853, in 2021 Rp. 19,071,950,542 and in 2022 Rp. 26,214,460,693. Keywords: Traffic Accident; Amount of Casualty Costs Accident; Z-Score; Kalianak Road; Tambak Langon – Osowilangun; Romokalisari Highway.